Indonesian Fine Art Terms and Their English Equivalence - Ronald Umbas; I Gusti Agung Sri Rwa Jayantini (Institut Seni Indonesia Denpasar, 2021)
The objective of this study is to identify the procedures of translation of fine art terms from English into Indonesian found in the catalog of Kun Adnyana's paintings entitled Candra Sangkala and to identify linguistic phenomena that arise from the translation. The catalog promotes the work of art and provides as much information as possible so that the work of the artist can be more widely appreciated. Therefore, the specific terms used in this fine art text should be translated appropriately in order to communicate the messages accurately, readably and naturally. The method used in this research was qualitative method which was conducted by doing content analysis in accordance with the theories of translation. This study found that the translation of fine art terms from Indonesian to English was conducted through seven procedures, namely couplet consisting of shift and reduction and expansion, second couplet, which is the combination of shift and literal translation, descriptive equivalent, reduction and expansion, literal translation, shift, and transference. The application of these procedures lead to two interesting phenomena that occur in the translation of Indonesian-English translation of fine art terms, i.e. (1) the use of equivalents that are previously naturalized from English into Indonesian and several terms that are literally translated and (2) the combination of more than one procedure of translation that is irrefutable in translating phrases. All of the procedures were utilized to meet the accuracy, naturalness and acceptability in translation.